Understanding the Thermal Regime of Rivers Influenced by Small and Medium Size Dams in Eastern Canada. (10th June 2016) - Maheu, A.; St‐Hilaire, A.; Caissie, D.; El‐Jabi, N.
Abstract: Although small and medium‐size dams are prevalent in North America, few studies have described their year‐round impacts on the thermal regime of rivers. The objective of this study was to quantify the impacts of two types of dams (run‐of‐river, storage with shallow reservoirs) on the thermal regime of rivers in eastern Canada. Thermal impacts of dams were assessed (i) for the open water period by evaluating their influence on the annual cycle in daily mean water temperature and residual variability and (ii) for the ice‐covered winter period by evaluating their influence on water temperature duration curves. Overall, results showed that the run‐of‐river dam (with limited storage capacity) did not have a significant effect on the thermal regime of the regulated river. At the two rivers regulated by storage dams with shallow reservoirs (mean depth < 6 m), the annual cycle in daily mean water temperature was significantly modified which led to warmer water temperatures in summer and autumn. From August to October, the monthly mean water temperature at rivers regulated by storage dams was 1.4 to 3.9°C warmer than at their respective reference sites. During the open water period, the two storage dams also reduced water temperature variability at a daily timescale while increased variability was observed in regulated rivers during the winter. Storage dams also had a warming effect during the winter and the winter median water temperature ranged between 1.0 and 2.1°C downstream of the two storage dams whereas water temperature remained stable and close to 0°C in unregulated rivers. The biological implications of the altered thermal regimes at rivers regulated by storage dams are discussed, in particular for salmonids. Copyright © 2016 John Wiley & Sons, Ltd.